Israel's contradictory gas export policy: The promotion of a transcontinental pipeline contradicts the declared goal of regional cooperation - Stefan Wolfrum (Stiftung Wissenschaft und Politik (SWP), 2019)
In order to market its gas reserves, Israel has until now relied on exports to Egypt and Jordan. Through regional networking in the energy sector - for example, within the framework of the Eastern Mediterranean Gas Forum (EMGF), which was founded at the beginning of 2019 - the Israeli government hopes to improve its political relations in the region. At the same time, Israel is investing hope in the building of the EastMed gas pipeline. Its construction would create a direct export link to Europe, but it would thereby also undermine energy cooperation with its Arab neighbours. The European Union (EU) should promote regional energy cooperation, as this could promote partnerships in other areas. Accordingly, the EU should not support the construction of the EastMed pipeline.
Keywords: 320